Exploring the best scenario for understanding the high temperature thermoelectric behaviour of Fe2VAl - Sk S.; Devi P.; Singh S.; Pandey S.K. (My University, 2025)
Heusler-type Fe2VAl compound is a promising thermoelectric candidate with non-magnetic ground state. The present work investigates the Seebeck coefficient (S) of Fe2VAl in the temperature region 300 to 620 K with the help of experimental and theoretical tools. The experimental value of S is observed ∼-130 μV/K at 300 K. Afterthat, the magnitude of S decreases gradually as the temperature increases. At T = 620 K, the value of S is found to be ∼-26 μV/K. In order to understand the behaviour of the experimentally observed S value, the band-structure and density of states calculations are performed by using LDA, PBE, PBEsol, mBJ and SCAN within density functional theory. All the above mentioned exchange-correlation (XC) functionals (except mBJ) predict the semi-metal like behaviour of the compound, whereas the mBJ gives the indirect band gap of ∼0.22 eV having the well agreement with experimentally observed value. The temperature dependence of S for Fe2VAl is also calculated with the help of all the five mentioned functionals individually. The best XC functional is investigated for searching the new thermoelectric materials by taking Fe2VAl as a case example through this study. The best matching between experimental and calculated values of S as a function of temperature is observed by setting the mBJ band gap with the band-structure of PBEsol or SCAN. Therefore, the present study suggests that the band-structure of PBEsol or SCAN with mBJ band gap can be used for searching the new thermoelectric materials. © 2018 IOP Publishing Ltd.